The Effect of Natural Material-Based Science Learning Media on the Science Skills of Children Aged 5–6 Years - caryati caryati; Sirojjudin Sirojjudin; Abdul Hafid (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aims to analyze the effect of using natural material-based science learning media on the science abilities of children aged 5–6 years. The main problem addressed in this study is the low level of children's science abilities, which are still dominated by conventional learning that lacks direct experiential engagement. This study employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The research subjects consisted of 31 children divided into two groups: the experimental group (16 children) and the control group (15 children). Data were collected using observation instruments and science ability tests covering indicators such as observing, classifying, conducting simple experiments, and drawing conclusions. The results showed that the mean posttest score of the experimental group (43.13) was higher than that of the control group (35.07). The independent sample t-test revealed a significant difference (p < 0.05) between the two groups. In addition, the N-Gain analysis indicated a high improvement in the experimental group (0.79) and a moderate improvement in the control group (0.48). These findings demonstrate that the use of natural material-based learning media effectively improves children's science abilities. In conclusion, natural material-based learning media have a significant effect on early childhood science abilities. The practical implication of this study highlights the importance of utilizing the surrounding environment as a contextual, effective, and economical learning resource. Theoretically, this study reinforces the concept of experience-based constructivist learning in early childhood education.